Nitrogen fertilization on off-season corn crop - Casagrande, João Reinaldo Ribas; Filho, Domingos Fornasieri (Pesquisa Agropecuaria Brasileira, 2002)
Experimental researches conducted with corn (Zea mays L.) on normal season in clay soils of tropical regions suggest that losses of the soil N forms are not significant by lixiviation, because the NH4+ form on the tropical soils is more stable than it was supposed. In addition it was physiologically determined that the N absorption is more intensive in the earlier stages of the plants. To evaluate the proposal of the N fertilization effect on corn cultivated on off-season crop, the sowing of two corn hybrids with genetic differences (single, C333B and double, C444) was done on February 3rd, 1999, on clay soil at FCAVJ-Unesp. Four rates of N (0, 30, 60 and 90 kg/ha), as urea, were applied at two times: sowing and after emergency when the plants were with five to six leaves. The harvest was done on July 7th, 1999, with the evaluation of agronomic characteristics and nutrient content on leaves. There was no effect on rate increase or the timing of application of the N fertilizer, for the agronomic characteristics like grain yield, one thousand grain mass, harvest index, ear and plant height, number of total grains and number of grain rows per ear. The foliar content of N, P, K, Ca, Mg, S and Zn were not influenced by the treatments because the values remained in the adequate rate scale.